Analisis Karakteristik Individu dan Modal Sosial Terhadap Partisipasi Masyarakat Dalam Pemanfaatan Dana Desa - Arna Suryani; Atikah Atikah (J-MAS (Jurnal Manajemen dan Sains), 2020)
The role and participation of villagers is needed for sustainable village development. The role and participation of the community is very important for the acceleration of development in the village, where village development can be realized by the involvement or participation of the community. This research was conducted in Muaro Jambi District of Sungai Gelam sub-district in Sungai Gelam village which aims to know and analyze whether there is a relationship between individual characteristics, and social capital to community participation judging by the utilization of village funds allocation. This study uses a list of questions (questionnaires) as a research instrument. The list of questions is organized according to the research variables and distributed directly to the respondent. The samples in this study were selected based on random sampling and selected as many as 20 research samples. The data is ordinal with nonparametric statistical analysis tools to see if there is a correlation between ordinal-scale variables. Based on the results prove that individual caraeristic and social capital have a positive and significant relationship with the strength of the relationship is strong enough to the participation of members in the utilization of village funds. The results of this study prove that the characteristics of individuals shown with high levels of education and high motivation as well as social capital owned by the community in the form of trust, networking and high norms are positively related to community participation in village development through planning, implementation, evaluation and monitoring until enjoying the results. The results of this study prove the role and participation of the community is needed in the utilization of village funds starting from how to plan, how the implementation stage, how the evaluation or monitoring stage up to the stage of enjoying the results and the availability of honest, correct and transparent financial statements in order to accelerate village development through the absorption of effective and efficient village funds.